Advanced Directives in Palliative Care - Shatri, Hamzah; Faisal, Edward; Putranto, Rudi; Sampurna, Budi (Jurnal Penyakit Dalam Indonesia, 2020)
Initially palliative care is emphasized at the end of life, but the right thing is to begin identifying palliative care needs when the disease is diagnosed. Palliative care is the treatment needed to improve the quality of life of patients and their families that suffering from life threatening and progressive disease such as cancer, non-cancer diseases, and HIV/AIDS (human immunodeficiency virus/acquired immunodeficiency syndrome). Palliative care decision must be in place from the beginning of treatment, so the patient’s preferences are met. The goals of this care are to reduce physical, social, psychological, and spiritual suffers. Further treatment plan is based on discussion between patient, family, and health care worker. The final result is identification and decision that can be written in advanced directives.